2022
DOI: 10.3390/jcm11133830
|View full text |Cite
|
Sign up to set email alerts
|

Moesin Serves as Scaffold Protein for PD-L1 in Human Uterine Cervical Squamous Carcinoma Cells

Abstract: Immune checkpoint blockade (ICB) therapy targeting the programmed death ligand-1 (PD-L1)/PD-1 axis has emerged as a promising treatment for uterine cervical cancer; however, only a small subset of patients with uterine cervical squamous cell carcinoma (SCC) derives clinical benefit from ICB therapies. Thus, there is an urgent unmet medical need for novel therapeutic strategies to block the PD-L1/PD-1 axis in patients with uterine cervical SCC. Here, we investigated the involvement of ezrin/radixin/moesin (ERM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Furthermore, they also showed a higher expression of PD-L1 in the tumor samples from patients with cervical SCC and a lower survival probability in the cervical SCC patients who had high moesin expression than those who had low/medium moesin expression. This was achieved using data from The Cancer Genome Atlas, partly supporting their idea that there is a possible correlation between PD-L1 and moesin in uterine cervical SCC [ 29 ].…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Furthermore, they also showed a higher expression of PD-L1 in the tumor samples from patients with cervical SCC and a lower survival probability in the cervical SCC patients who had high moesin expression than those who had low/medium moesin expression. This was achieved using data from The Cancer Genome Atlas, partly supporting their idea that there is a possible correlation between PD-L1 and moesin in uterine cervical SCC [ 29 ].…”
mentioning
confidence: 79%
“…Similarly, Tameishi M. and Ishikawa H. et al found that ezrin also contributes to the cell surface plasma membrane localization of PD-L1 in the human epithelial ovarian cancer cell line A2780 cells [ 28 ]. Subsequently, Doukuni R. and colleagues demonstrated that in the human cervical squamous cell carcinoma (SCC) BOKU and HCS-2 cell lines, plasma membrane co-localization and protein–protein interaction of PD-L1 takes place with all three ERM proteins by means of immunofluorescence microscopy or co-immunoprecipitation experiments using a specific antibody against PD-L1, respectively [ 29 ]. Intriguingly, Doukuni R. et al discovered that RNAi-mediated knockdown of moesin—but not ezrin and radixin—significantly reduced the cell surface expression of PD-L1 with little impact on its mRNA expression, illuminating the unexpected role of moesin in the plasma membrane localization of PD-L1, possibly via post-translational modification process, as it served as a scaffold protein in the human cervical SCC [ 29 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 23 ] found that the combination of TILs and anti-PD1 significantly improves the prognosis of metastatic cervical cancer. However, only a small proportion of patients with squamous cell carcinoma (SCC) of the uterine cervix derive clinical benefits from ICB therapy [ 24 ]. A study by Ari found that 30% of cervical malignancies are positive for cytotoxic T-lymphocyte antigen 4 (CTLA4) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ezrin/radixin/moesin (ERM) family members are the three closely related proteins that post-translationally modulate the cellular membrane localization of numerous cancer-related transmembrane proteins by crosslinking with the actin cytoskeleton [ 19 , 20 , 21 , 22 ]. Our laboratory recently demonstrated that the ERM family post-translationally modulates the cellular surface localization of PD-L1, which belongs to a group of IgG superfamilies similar to CD47, by serving as a scaffold protein in several cancer cell types, including PDAC [ 23 , 24 , 25 , 26 , 27 ]. However, it is unclear whether the ERM family is involved in the cellular membrane localization of CD47 through post-translational modifications in cancer cells.…”
Section: Introductionmentioning
confidence: 99%